The Impact Of Artificial Intelligence On Consumer Behavior: A Comprehensive Review Of Marketing Strategies In The Digital Age - Mahadewi, Erlina Puspitaloka; Sanantagraha, Arnastya Iswara; Sugiharto, Amo (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
The advancement of Artificial Intelligence (AI) technology has brought significant changes to consumer behavior and marketing strategies in the digital age. This study aims to provide a comprehensive review of the impact of AI on consumer behavior while exploring marketing strategies adopted by businesses to address these changes. By utilizing literature analysis from recent journals, books, and scholarly articles, this research highlights how AI technologies—such as predictive algorithms, personalization, and chatbots—affect consumer decision-making processes, enhance customer experiences, and accelerate purchasing behaviors. On the other hand, AI also introduces new challenges related to privacy, ethics, and consumer trust in technology. The findings of this study reveal that companies successfully implementing AI into their marketing strategies are able to foster closer relationships with customers through more relevant and data-driven interactions. In this context, the role of technology in understanding consumer needs and preferences becomes a key driver of marketing success. This study provides valuable insights for academics and practitioners on how AI is transforming the marketing and consumer behavior landscape, while also recommending best practices for leveraging this technology. As such, this research emphasizes the importance of adapting to AI technologies to create added value in an increasingly competitive market.